Children's Health and Well-being during the COVID-19 Pandemic in Japan - Naoki Nakamura (Asian Social Work Journal, 2021)
The COVID-19 has caused challenges at all levels of society. It is necessary to, while carefully looking at impact that COVID-19 will have on children's health and well-being, and to steadily implement social work services accordingly. This paper highlights some key challenges and concerns for health and well-being on children and adolescents in Japan during COVID-19 pandemic. The purpose of this paper is to consider how the COVID-19 pandemic and the policy taken to mitigating the risk of COVID-19 have impacted children in Japan. In conclusion, we are not saying that COVID-19 policy responses such as school closures overall are ineffective for mitigating the COVID-19 pandemic in Japan. However, as we have seen, school closing policy is likely to have a negative impact on children’s health and well-being such as increased risks of mental health, abuse and suicide. The important point is that these impacts is not the impact of COVID-19 but the impact of the policy responses to COVID-19. The policy responses are likely to lead to a range of unexpected impacts and results. Therefore, policy makers, social workers and other professionals always should consider for the impact of policy responses to COVID-19 on children and adolescents.